Faktor Risiko Kanker Serviks: Literature Review - Umu Khabibah; Kartika Adyani; Alfiah Rahmawati (Universitas Faletehan, 2022)
Cervical cancer is caused by infection with the Human Papilloma Virus (HPV) which grows in the cervix resulting in malignant tumors. Cervical cancer is the fourth most common cancer in women in the world. The purpose of this study was to determine the risk factors for cervical cancer. With the incidence of cervical cancer in the community, this study used a literature study. The search used PubMed and Google Scholar databases from 2017 to 2020 publication years and found 12 relevant articles based on the inclusion criteria. The results of the review showed that cervical cancer can be caused by risk factors of early sexual activity, use of tobacco cigarettes, use of hormonal contraception, and having > 1 sexual partner. There was a relationship between risk factors of cervical cancer between engaging in sexual activity at an early age (<20 years), using tobacco cigarettes, using hormonal contraception ≥5 years, and having >1 sexual partner. It was important for medical personnel and health care facilities to use an approach of providing education to people about cervical cancer risk factors to make them knowing the impacts, dangers and preventions of cervical cancer.